2014
DOI: 10.1016/j.gie.2014.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Low uptake of colorectal cancer screening among African Americans in an integrated Veterans Affairs health care network

Abstract: Background African Americans have the highest incidence and mortality from colorectal cancer (CRC). Despite guidelines to initiate screening with colonoscopy at age 45 in African Americans, CRC incidence remains high in this group. Objective To examine rates and predictors of CRC screening uptake as well as time-toscreening in a population of African Americans and non-African Americans in a healthcare system that minimizes variations in insurance and access. Design Retrospective cohort study. Setting Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
(26 reference statements)
1
38
0
4
Order By: Relevance
“…Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit.…”
Section: Discussionmentioning
confidence: 99%
“…3 Primary care providers (PCP) traditionally initiate cancer screening, and prior work has shown that patients seen by PCPs are more likely to receive CRC screening. [4][5][6][7][8] However, CRC screening rates remain suboptimal, even after decades of public health campaigns, public reporting of health plan CRC screening rates, and implementation of visitbased preventive service reminders in electronic health records (EHRs). 4,7,[9][10][11] Therefore, a growing number of private and public health systems are taking a population health perspective and using outreach approaches to promote CRC screening that do not require a face-to-face primary care visit.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the 2010 Behavioral Risk Factor Surveillance Survey revealed that 62% of non-Latino whites were up-to-date for colorectal cancer screening compared to 31% of Spanish-speaking Latinos, 47% of Asians, and 59% of African Americans 12 . A recent study conducted in the VA revealed significantly lower colorectal cancer screening rates among African Americans (42%) compared to non-African American veterans (58%) despite similar access to screening 13 . Observational studies, mainly focusing on Whites, suggest that CRC screening rates tend to be only somewhat higher among FDRs compared to average risk individuals 14 .…”
Section: Introductionmentioning
confidence: 95%
“…African Americans are also less likely to adhere to colonoscopy than whites when recommended for screening 8-10 . Our research group has demonstrated differences in the use of colonoscopy for colorectal cancer (CRC) screening in a large and demographically diverse Veterans Affairs Healthcare Network (VA) where uptake of colonoscopic screening was significantly lower in eligible African American veterans than white veterans in a retrospective analysis of CRC screening utilization 11 . These inequities existed despite a known higher risk of CRC among African Americans and guidelines from the American College of Gastroenterology to preferentially screen for CRC with colonoscopy in African Americans 12 .…”
Section: Introductionmentioning
confidence: 99%